Combination of Gefitinib and Pemetrexed Prevents the Acquisition of TKI Resistance in NSCLC Cell Lines CarryingEGFR‐Activating Mutation. Issue 7 (July 2016) - La Monica, Silvia; Madeddu, Denise; Tiseo, Marcello; Vivo, Valentina; Galetti, Maricla; Cretella, Daniele; Bonelli, Mara; Fumarola, Claudia; Cavazzoni, Andrea; Falco, Angela; Gervasi, Andrea; Lagrasta, Costanza Annamaria; et al.
ABSTRACT : Introduction: : Development of resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors is a clinical issue in patients with epidermal growth factor receptor gene ( EGFR )‐mutated non–small cell lung cancer (NSCLC). The aim of this study was to investigate the potential of combining gefitinib and pemetrexed in preventing the acquisition of resistance to EGFR tyrosine kinase inhibitors in NSCLC cell lines harboring EGFR exon 19 deletion. Methods: : The effect of different combinatorial schedules of gefitinib and pemetrexed on cell proliferation, cell cycle, apoptosis, and acquisition of gefitinib resistance in PC9 and HCC827 NSCLC cell lines and in PC9 xenograft models was investigated. Results: : Simultaneous treatment with gefitinib and pemetrexed enhanced cell growth inhibition and cell death and prevented the appearance of gefitinib resistance mediated by T790M mutation or epithelial‐to‐mesenchymal transition (EMT) in PC9 and HCC827 cells, respectively. In PC9 cells and in PC9 xenografts the combination of gefitinib and pemetrexed, with different schedules, prevented gefitinib resistance only when pemetrexed was the first treatment, given alone or together with gefitinib. Conversely, when gefitinib alone was administered first and pemetrexed sequentially alternated, a negative interaction was observed and no prevention of gefitinib resistance was documented. The mechanisms of resistance that developed in vivo included T790M mutation and EMT. The induction of EMT was a feature of tumors treated with gefitinib when given before pemetrexed, whereas T790M was recorded only in tumors treated with gefitinib alone. Conclusions: : The combination of gefitinib and pemetrexed is effective in preventing gefitinib resistance; the application of intermittent treatments requires that gefitinib not be administered before pemetrexed.